Dual Class Ownership and Tax Avoidance - McGuire, Sean T.; Wang, Dechun; Wilson, Ryan J. (The Accounting Review, 2014)
ABSTRACT: This study investigates whether the agency conflicts inherent in a dual class ownership structure are associated with the level of firms' tax avoidance. Dual class ownership presents a unique agency problem because insiders control a majority of the votes of a firm despite having claims to a minority of the firm's cash flows. We examine the level of tax avoidance for a sample of dual class firms and find that the extent of tax avoidance declines as the difference between voting rights and cash flow rights increases. We also compare the level of tax avoidance of dual class firms to a sample of propensity matched single class firms and find that dual class firms engage in less tax avoidance as the wedge between insiders' voting rights and cash flow rights increases. These findings are consistent with dual class ownership entrenching managers and allowing them to perform at a suboptimal level. Data Availability: Data used in this study are available from public sources identified in the paper.